Dampak Peningkatan Upah Minimum Provinsi Terhadap Inflasi Dan Pasar Kerja Di Provinsi Aceh - Safrida Safrida; Sofyan Sofyan; Nura Syahriani (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2014)
ABSTRACT. This research was conducted in the Province of Aceh. The purpose of this study was to analyze the factors that affect inflation, the provincial minimum wage, labor supply and labor demand in the Province during the period from 1998 to 2012. The data used in this study is secondary data time series obtained from the Central Statistics Agency of Aceh, Department of Labor and Population Mobility Aceh, Department of Trade and Industry Aceh and Aceh Pertamina. The model used is the model of simultaneous equations by the method of 2SLS (Two Stage Least Square) is used to analyze the function of each equation in this study. The results showed that the provincial minimum wage impact on inflation and the increase in labor supply and the impact on the demand for labor in the province. Economically, the regression results indicate that for each of the variables that affect inflation, the provincial minimum wage, labor supply and demand in the province of Aceh has not been all in accordance with the sign the expected coefficients and variables in each equation only population significant effect on labor supply, whereas the other variables did not significantly affect the endogenous variables. However, simultaneous testing for functionality inflation equation has no real effect, whereas the function of the provincial minimum wage equations, labor supply and labor demand in the province has a real impact.